Long Term Neuropsychological Follow-Up in Patients With Herpes Simplex Encephalitis and Predominantly Left-Sided Lesions - B. Laurent; R. F. Allegri; C. Thomas-Anterion; N. Foyatier; B. Naegele-Faure; J. Pellat (Behavioural Neurology)
Five patients with predominantly dominant cerebral hemisphere lesions due to herpes simplex encephalitis are described. Verbal amnesia was the main deficit but amnesic aphasia sometimes associated with impairment of remote memory also occurred. Semantic and episodic memory deficits were also explored in one case and the role of the right cerebral hemisphere in facilitating recovery of learning is discussed.